Creatine supplementation and the role on oxidative stress, brain creatine level and inflammation. A brief review - Moscatelli, Fiorenzo; Villano, Ines; Monda, Marcellino; Messina, Antonietta; Monda, Vincenzo; Cibelli, Giuseppe; Valenzano, Anna; Tartaglia, Nicola; Ambrosi, Antonio; Porro, Chiara; Messina, Giovanni (Progress in Nutrition, 2022)
One of the most important and popular nutritional ergogenic aids for athletes is creatine. Numerous scientific studies have shown that the constant supplementation of creatine favors the increase of its concentration in the muscles, and this could lead to an increase in physical performance, especially of high intensity exercises. Additionally, creatine supplementation appears to be related to improved post-exercise recovery, injury prevention, thermoregulation, rehabilitation, and neuroprotection of concussion and / or spinal cord. From these studies it is found that the intake of creatine, in addition to beneficial effects on sports performance, can have post-injury effects and improve injury-recovery, increasing the tolerance of athletes loaded with heavy training. Additionally, several studies have shown numerous potential beneficial effects of creatine supplementation. In this investigation was show that short and long-term supplementation (up to 30 g/day for 5 years) is safe and well-tolerated in healthy individuals and in a number of patient populations ranging from infants to the elderly. Moreover, significant health benefits may be provided by ensuring habitual low dietary creatine ingestion (e.g., 3 g/day) throughout the lifespan. The aim of this brief review is to provide an overview to the current literature regarding the role and safety of creatine supplementation in exercise, and the role on oxidative stress, brain cretine level and inflammation.